Application Of Stad Learning Method By Using Picture Methods In Interactive Learning Can Improve Results Of Student Science - Jasni Elti (Jurnal Ilmiah Pendidikan Scholastic, 2018)
To learn a lesson well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, teachers need to "do it", that is to describe something in their own way, to show their example, to try to practice their skills and to do tasks that demand the knowledge they have gained. Problems to be studied in this research are: Does using the application of STAD learning method using image method can improve science learning outcomes of students of class VIII SMPN 1 Coastal Ranah? Steps taken in using STAD method?. This research was conducted in Class VIII SMP Negeri 1 Coastal Ranah in 2016. As a place used to obtain the desired data. This research was conducted in January 2016 until February 2016. The research subjects were students of Class VIII SMP Negeri 1 Ranah Pesisir in January 2016. This study used Classroom Action Research (PTK). A TOD is a reflective form of study by actors undertaken to enhance the rational stability of their actions in carrying out the task, deepening the understanding of the actions taken, and improving the conditions in which such learning practices are conducted (in Mukhlis 2000: 3) . Based on the results of learning activities that have been conducted during the study, and based on all the discussion and analysis that has been done can be concluded as follows: 1. Learning by STAD method in science lessons have a positive impact in improving student achievement marked by students' learning mastery in learning (97,29%) 2. Application of STAD media method in science lesson have positive influence, that is can improve student's learning motivation which is indicated by average 80 and from interview result stating that students are interested and interested with cooperative method of learning science become motivated to learn.